Scientific Realism and Primitive Ontology Or: The Pessimistic Induction and the Nature of the Wave Function - Allori, Valia (Lato Sensu: Revue de la Société de philosophie des sciences, 2018)
In this paper, I wish to connect the recent debate in the philosophy of quantum mechanics concerning the nature of the wave function to the historical debate in the philosophy of science regarding the tenability of scientific realism. Advocating realism about quantum mechanics is particularly challenging when focusing on the wave function. According to the wave function ontology approach, the wave function is a concrete physical entity. In contrast, according to an alternative viewpoint, namely the primitive ontology approach, the wave function does not represent physical objects. In this paper, I argue that the primitive ontology approach can naturally be interpreted as an instance of the so-called explanationist realism, which has been proposed as a response to the pessimistic-meta induction argument against scientific realism. If my arguments are sound, then one could conclude that: (1) contrary to what is commonly thought, if explanationism realism is a good response to the pessimistic-meta induction argument, it can be straightforwardly extended also to the quantum domain; (2) the primitive ontology approach is in better shape than the wave function ontology approach in resisting the pessimistic-meta induction argument against scientific realism.